ANALISIS DINAMIKA KELOMPOK PEMBUDIDAYA IKAN HIAS AIR TAWAR DI KOTA PEKANBARU PROVINSI RIAU - Siha Simbolon; Viktor Amrifo; Kusai Kusai (Berkala Perikanan Terubuk, 2017)
This research was conducted on 27 February - 23 March 2016 for the city of Pekanbaru in Riau Province. The research objective to describe groups of farmers of freshwater fish, to compare the dynamics between groups of farmers ornamental fish are nurtured and is not fostered Department of Agriculture and analyze the elements of group dynamics farmers freshwater fish are nurtured and is not supervised by the Department of Agriculture. Determination of the respondents were proportional sampling with the taking of respondents as many as 18 people from the group of respondents ornamental fish farmers who belong to a group that fostered and nurtured a group that is not the Department of Agriculture. Analysis of the dynamics of the group performed that the group fostered by the Department of Agriculture has a score of 122.2 which is the level of dynamics in the dynamic category, while the ornamental fish farmers do not fostered scores 89.2 dynamics that are in the category of dynamic enough. this is because the group is fostered by the department of agriculture has a role in fostering a more ornamental fish farmers groups, and all elements of the group have a desire to grow their businesses as seen from the effectiveness of the groups that affect the dynamics of the group as the elements of goal attainment and satisfaction of group members.